Implementation Of E-Continued Professional Development (E-CPD): Issues And Challenges - Rafiza, A.R.; Shaharom, M.S.N.; Yusop, F.D.
This paper looks into the challenges in implementing e-continued professional development (e-CPD) for teachers designing creative multimedia products for instructional purposes. Data collection was carried out via qualitative methodology applying two techniques; interview and document analysis. Four in-service teachers involved in the interview. The data was further supported by findings from analysis on the teachers’ participation log online. The research findings revealed issues in implementing e-CPD among teachers such as deficiency in terms of technical skills, experience and time management. Thus, upon designing e-CPD for teachers, instructional designers should consider analyzing the teachers’ need taking into consideration the deficiencies discussed. Copyright@ 2014 University of Malaya all right reserved